Combination of Bawang Dayak Extract and Acarbose against Male White Rat Glucose Levels - Aditya Maulana Perdana Putra; Ratih Pratiwi Sari; Siska Musiam (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Diabetes is a chronic metabolic disease with signs of increased blood glucose levels. Type 2 diabetes is common diabetes in adults. Bawang dayak is one of the plants believed to have the efficacy of curing various types of diseases. The purpose of this study was to find out the comparison of hypoglycemic effects between combinations of bawang dayak extract and acarbose with single acarbose. This study was an experimental study using 32 white mice divided into two groups. Group one was given a combination of bawang dayak at a dose of 100 mg/kg BW and acarbose at a dose of 40 mg/100 g BW, while group two was given acarbose at a dose of 40 mg/100 g BW. Treatment is administered after the test animal is induced with dexamethasone at a 1 mg/kg BW dose dissolved in NaCl 0.9% subcutaneously for 12 days. Measurement of glucose levels was carried out using a glucometer. Data retrieval was carried out every three days for 15 days after previously fulfilled for +10 hours. Blood glucose level data were analyzed with the General Linear Model test. The combination of bawang dayak-acarbose onion extract had a greater decrease in blood glucose levels than single acarbose. Average reduction in blood glucose levels for D+3; D+6; D+9; D+12; and D+15 was 187.31; 168.56; 140.81; 119.81; and 102.56 mg/dl, respectively. The General Linear Model test results showed a p <0.05 value that significantly impacted blood glucose levels between groups.